Seismicity-based 3D model of ruptured seismogenic faults in the North-South Seismic Belt, China - Rong, Yilin; Bai, Yongliang; Ren, Mengjiao; Liang, Mingjian; Wang, Zhenjie (Frontiers in Earth Science, 2023)
The North–South Seismic Belt produces the most frequent strong earthquakes in the Chinese continental region, such as the MS 8.0 Wenchuan earthquake on 12 May 2008 and Ms 7.0 Lushan earthquake on 20 April 2013. This seismicity results in significant hazards. Fault geometry modeling is crucial for analyzing earthquake preparation and trigger mechanisms, simulating and predicting strong earthquakes, inverting fault slip rates, etc. In this study, a novel method for obtaining geometric models of ruptured seismogenic faults over a large area is designed based on datasets from surface fault traces, fault orientations, focal mechanism solutions, and earthquake relocations. This method involves three steps. 1) An initial model of the fault geometry is constructed from the focal mechanism solution data. This initial model is used to select the earthquake relocation data related to the target fault. 2) Next, a fine model of the fault geometry with a higher resolution than that of the initial model is fitted based on the selected earthquake relocation data. 3) The minimum curvature interpolation method (Briggs, 2012) is adopted to build a 3D model of the subsurface fault geometry according to the three-dimensional coordinates of nodes on all profiles of each fault/segment. Based on this method and data collected in the North–South Seismic Belt, the fine morphologies of different faults along 1,573 transverse profiles were fitted, and a 3D model of 263 ruptured seismogenic faults or fault segments in the North–South Seismic Belt was built using the minimum curvature spatial interpolation method. Since the earthquake number decreases with increasing depth, the model uncertainty increases with increasing depth. Different ruptured faults have different degrees of seismicity, so different fault models may have different uncertainties. The overall fitting error of the model is 0.98 km with respect to the interpreted results, from six geophysical exploration profiles.